Monitoring development from 0–6 years: an online system, standardized for Dutch children - Van Baar, Anneloes; Verhoeven, Marjolein; Hessen, David; de Paauw-Telman, Liesbeth; Krijnen, Lisa (Frontiers in Developmental Psychology, 2025)
BackgroundMonitoring and screening children's development from infancy into early childhood is important for prevention purposes, as potential delay may best be addressed as soon as possible. For an efficient monitoring system, standardized online tools with population specific norm scores are needed. An online system, “Ontwikkeling Voorop! 0–6,” was created to evaluate Communication, Gross and Fine Motor functioning, Problem Solving and Personal-Social Behavior of children aged 0–6, using caregiver reports.MethodsPilot studies evaluated the first versions of the system. Next, data were collected of a representative sample of 1690 Dutch children aged 0-6 years (mean = 24.6 months, SD = 19.1, 50.5% male). Norm scores were modeled for each developmental domain on the conditional distribution of the total raw scores based on the children's age. Reliability and validity of the system was investigated.ResultsNorm scores on a scale from 0–100 centiles were created per age in months. Internal consistency measures (ω = 0.88–0.93 per domain) as well as repeated and inter-rater assessments indicated good reliability with moderate to strong correlations. Convergent validity was sufficient, with moderate to strong correlations between the results of the monitoring system and the Bayley-III-NL, WPSSI-IV-NL and Schlichting test for domains measuring similar constructs. Cut-off scores based on the 3rd, 10th and 90th centiles can be used to identify children in need of attention.DiscussionThe online system is a feasible and efficient way to monitor development of young children. It has standardized norm scores that are reliable and valid for the Dutch population.